Design of a CMOS dynamic reference ADC - Fan, Chao (2013)
This report describes a detailed approach to design an 8-bit dynamic reference analog-to-digital converter (ADC). The converter is designed based on the Charter 0.18 um processing technology. The design tools used in the project are Cadence Virtuoso schematic editor and Virtuoso Analog Design Environment. Some of the simulation data is analyzed with the assistance of MATLAB.